Pleiotropic Mitochondria: The Influence of Mitochondria on Neuronal Development and Disease - Rangaraju, Vidhya; Lewis, Tommy L., Jr.; Hirabayashi, Yusuke; Bergami, Matteo; Motori, Elisa; Cartoni, Romain; Kwon, Seok-Kyu; Courchet, Julien (Society for Neuroscience, 2019)
Mitochondria play many important biological roles, including ATP production, lipid biogenesis, ROS regulation, and calcium clearance. In neurons, the mitochondrion is an essential organelle for metabolism and calcium homeostasis. Moreover, mitochondria are extremely dynamic and able to divide, fuse, and move along microtubule tracks to ensure their distribution to the neuronal periphery. Mitochondrial dysfunction and altered mitochondrial dynamics are observed in a wide range of conditions, from impaired neuronal development to various neurodegenerative diseases. Novel imaging techniques and genetic tools provide unprecedented access to the physiological roles of mitochondria by visualizing mitochondrial trafficking, morphological dynamics, ATP generation, and ultrastructure. Recent studies using these new techniques have unveiled the influence of mitochondria on axon branching, synaptic function, calcium regulation with the ER, glial cell function, neurogenesis, and neuronal repair. This review provides an overview of the crucial roles played by mitochondria in the CNS in physiological and pathophysiological conditions.